Glycogen synthase kinase-3 as a key regulator of cognitive function. (6th March 2020) - Fan, Xuhong; Zhao, Zhenyu; Wang, Deming; Xiao, Ji
Abstract: Glycogen synthase kinase-3 (GSK-3) is a highly conserved and multifunctional serine/threonine protein kinase widely distributed in eukaryotic cells. GSK-3 is originally thought to be an enzyme that regulates glycogen synthesis. It was subsequently found that GSK-3 influences many critical cellular functions, such as cell structure, neural plasticity, gene expression, and neuronal survival. Recently, GSK-3 has been found to be associated with cognition, and its dysregulation leads to cognitive impairments in many diseases, including Alzheimer's disease, diabetes, depression, Parkinson's disease, and others. In this review, we summarized the current knowledge about the structure of GSK-3, the regulation of GSK-3 activity, and its role in cognitive function and cognitive-related disease.